(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Liver is a primary organ involved in metabolism of food and drugs. Liver disorders are mainly caused by toxic chemicals, such as antibiotics, chemotherapeutic agents, peroxidised oil, aflatoxin, carbon tetrachloride, chlorinated hydrocarbons etc. Toxic liver injury produced by drugs and chemicals may virtually mimic any form of naturally occurring liver disease. In view of multiplicity and complexity of the liver functions, it is obvious that no single test can establish the disturbances in liver function. Thus, a battery of liver function tests is employed for accurate diagnosis, to assess the severity of damage, to judge prognosis and to evaluate therapy. To study hepatoprotective potential of any herbal product, isolated phytochemical or synthetically developed moiety induction of experimental liver damage is prerequisite. The selection of toxicant depends on type and nature of liver damage required as every toxicant has its unique mode of action producing specific type of destruction. The hepatoprotective mechanism of any drug under study can be explained based on its protective behavioragainst different toxicants. This review is precise compilation of experimental liver pharmacology taking concern dose, route, and schedule of different liver toxicants along with evaluation biochemical, histological and functional ability parameters. The literature compilation will definitely help researcher in design and assessment of studies involving liver function.